PENGARUH TANGGUNG JAWAB MORAL, SANKSI PERPAJAKAN, DAN PENERAPAN SISTEM E-FILLING TERHADAP KEPATUHAN WAJIB PAJAK DALAM PENYAMPAIAN SURAT PEMBERITAHUAN (SPT) TAHUNAN PADA KPP PRATAMA BATAM UTARA (Studi Empiris Pada Wajib Pajak Orang Pribadi Yang terdaftar di KPP Pratama Batam Utara Tahun2016) - Eka Kurniawan; Zirman Zirman; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the effect of moral responsibility, tax sanctions, and e-filling system application on compulsary tax on insert letter of annual notice (SPT) in KPP Pratama Batam Utara. The Population of this study is on individual taxpayers registered in KPP Pratama Batam Utara in 2016. Data of this study was analyzed by using multiple regression method using SPSS (Statistical Product and Service Solution) version 25. The results showed that the effect of moral responsibility and tax sanctions did not affect on the compulsory of compulsory tax on insert letter of annual notice (SPT) and e-filling system application affect on compulsory of compulsory tax on insert letter of annual notice (SPT).Keywords : effect of moral responsibility, tax sanctions, and e-filling system application, compulsory of compulsory tax on insert letter of annual notife.